Gene diagnosis and pedigree analysis of two Han ethnicity families with propionic acidemia in Fujian. Issue 10 (12th March 2021) - Chen, Yao; Lin, Xuehua; Lin, Qingying; Zeng, Yinglin; Qiu, Xiaolong; Liu, Guanghua; Zhu, Wenbin
Abstract : Abstract: Propionic acidemia is associated with pathogenic variants in PCCA or PCCB gene. We investigated the potential pathogenic variants in PCCA or PCCB genes in Fujian Han population. Two probands and their families of Han ethnicity containing two generations were subject to newborn screening using tandem mass spectrometry, followed by diagnosis using urine gas chromatography mass spectrometry. Sanger sequencing was used to identify potential mutations in PCCA and PCCB genes. Compound heterozygous variants were identified in PCCB gene in two siblings of the first family, the youngest girl showed a novel missense variant c.1381G>C (p.Ala461Pro) in exon 13 and a heterozygous missense variant c.1301C>T (p.Ala434Val) in exon 13, which were inherited respectively from their parents. The oldest boy is a carrier with a novel missense variant c.1381G>C (p.Ala461Pro) in exon 13 which were inherited from his father. In the second family, c.1535G>A homozygous mutations were identified in the baby girl, which were inherited respectively from their parents. In silico analysis, several different types of bioinformatic software were utilized, which predicted that the novel variant c.1381G>C in PCCB gene was damaged. According to ACMG principle, the missense variant c.1381G>C (p.Ala461Pro) in exon 13 was a Variant of Undetermined Significance (VUS). One novel missense variant and two missense variants in PCCB gene were identified in the study. The novel variant of PCCB gene identified VUS was identified for the first time in the Chinese population, which enriched the mutational spectrum of PCCB gene.